Fatores Psicossociais no Trabalho da Enfermagem em Pronto-Socorro de um Hospital de Clínicas de Grande Porte - Nunes, Wilma da Silva (2017)
Introduction: The conditions and forms of organization of the work process can establish situations that are favorable to the individuals or constitute risk factors for their physical and mental health. Among the work environments, the health services, and more specifically the hospital, constitute a possibly stressful workplace due to its peculiar characteristics; the emergency unit can be considered one of the environments in which nursing professionals are subjected to greater psychic suffering due to the dynamics of this service. Objective: to identify and describe the psychosocial factors that the emergency room nursing staff are submitted to. Materials and Methods: a cross-sectional analytical study with a quantitative approach, carried out in September 2016 with 136 professionals, 23 nurses, 73 nursing technicians and 38 nursing assistants. A questionnaire was used for occupational socio-demographic characterization of the participants and the Job Content Questionnaire (JCQ) was used to characterize the psychosocial aspects of the work. The data were analyzed statistically using electronic spreadsheets, summarized by means of descriptive statistics and presented in tables. Results: as for the profile of the respondents, the majority were female (71.76%), who had been in the Emergency Room for 5 years or more (59.13%), is a nursing technician or assistant (81.02%), statutory (62.04%),has a graduate degree (59.13%), works in the day shift (48.18%), has a workload of 36 hours (100%), does overtime (66.4%) and / or has other employment (20.30%). With regard to the psychosocial aspects of the work, most of the interviewees identified the existence of negative aspects related to the psychological, physical and control demands on the work, such as repetitive work, high skill requirement, excessive volume of work, conflicting demands , unwanted changes, fast work, need for emotional control, hard work, a lot of physical effort, fast and continuous physical activity, work in uncomfortable positions, lack of autonomy and difficulty sleeping if you fail to do some task. With regard to social support, both from the top hierarchical levels and from their co-workers, several positive aspects were identified: the boss worries about the well-being of his work team, being treated with respect by the supervisor, being helped by the boss in doing the job, having the respect they deserve from bosses and supervisors; working involves a lot of negotiation, friendly and collaborative colleagues, having the respect of your coworkers, feeling of union between people. Most people consider themselves to be stable in their employment, are satisfied with their work, with their ability to work and consider their quality of life good or very good.Conclusions: the research showed that some issues related to the organization and the Nursing work process in the PSHC / UFU constitutes risk factors for the physical and mental health of professionals. It is suggested that strategies be developed to monitor psychosocial risks, as well as prevention campaigns, spaces for discussions, suggestions and denunciations about the organizational climate, as well as treatment and follow-up of professionals affected by negative psychosocial factors.